2007
DOI: 10.1177/0145482x0710100702
|View full text |Cite
|
Sign up to set email alerts
|

Accessible GPS: Reorientation and Target Location among users with Visual Impairments

Abstract: The recent explosion in the use of global positioning satellite technology has significantly increased people's ability to maintain place orientation and to store and retrieve information about specific locations, such as businesses, recreational facilities, and geographic attributes (Broida, 2004; El-Rabbany, 2002). Rather than relying on the floating bubblelike compass that once sat on the dashboard and gave a rough estimate of the direction of travel, when a person prepares for a trip to grandmother's house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Such systems provide in situ navigation instructions enabling faster navigation [25] with fewer halts [16]. A number of different systems have been explored, with most of them based on GPS technology, to present navigation and wayfinding information to the user.…”
Section: Related Workmentioning
confidence: 99%
“…Such systems provide in situ navigation instructions enabling faster navigation [25] with fewer halts [16]. A number of different systems have been explored, with most of them based on GPS technology, to present navigation and wayfinding information to the user.…”
Section: Related Workmentioning
confidence: 99%
“…The visually impaired is more vulnerable to collision, especially when crossing an intersection, due to insufficient information concerning traffic, walk phase, and intersection geometry. 7 A seemingly effortless crossing at intersection for sighted pedestrians has been proven considerably difficult for the visually impaired. The subtasks involving in crossing a street can be broken down to 1) detecting the existence of an intersection, 2) determining the street or direction (heading) to cross, 3) locating the crosswalk, 4) aligning the heading with the destination, and 5) maintaining a straight path during crossing within a crosswalk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MOBIC dialogue system introduces multi-tiered directions that provide progressively more detailed information about a scene [9]. Recent work has found that visually impaired individuals using navigation devices travel to new areas faster [4] and with less errors and halts [5] than using Physical maps or direct experience. Sendero [6] uses smart phone's location sensing power.…”
Section: Literature Reviewmentioning
confidence: 99%